Students' Perceptions Of Educational Disparities Among Students In Urban And Rural Areas Of Muara Enim Regency - Meiwin Virga; Salsabila Salsabila; Zidni Ma’ruf; M.Kelfin Handaresta (JUPE : Jurnal Pendidikan Mandala, 2026)
The study was conducted to explore students' perceptions about the gulf of education between urban and rural areas in the Muara Enim district. Qualitative descriptive method is used in the study by involving six high school students as participants. Data collection is conducted through semi-structured interviews to obtain information about the students' experiences and views of the education conditions in both areas. Research results suggest that availability of facilities, accessibility, technological support and Internet connectivity in urban areas are more adequate than rural areas, such as limitations in facilities, inadequate infrastructure lack education, and unstable Internet access, they are perceived to affect experiences in learning and students' opportunities for quality education.. Thus, increased education infrastructure and the equalizing of educational resources should be made in an effort to reduce educational inequality and realize more equitable learning opportunities for all students.